Sign language, sustainable development, and equal opportunities : envisioning the future for deaf students - De Clerck, Goedele; Paul, Peter V. (Gallaudet University Press, 2016)
"Increased interaction between sign language communities and the mainstream societies in which they function is creating the potential for greater equality of opportunity for people who are deaf and hard of hearing. In this volume, renowned scholars and policy makers from around the world present innovative and groundbreaking perspectives on the relationships among sign language, sustainable development, and equal opportunities. The contributors to this volume offer creative and open-minded explorations of the construct of sustainability that are informed by their work with deaf individuals, deaf communities, families of deaf children, and other stakeholders. Sign Language, Sustainable Development, and Equal Opportunities describes sustainability in relation to: · identity, resilience, and well-being ·particƯipatory citizenship ·historical perspectives on sign language use in educational contexts ·sign language learning and teaching ·human rights and inclusive education ·literate thought and literacy ·the sign language factor and the development of sign language communities in sub-Saharan Africa ·sign language legislation These changing communities' understanding of what is required to become sustainable--in areas such as full participation and citizenship in society, economic well-being, access to quality education, and cultural and linguistic identity--is also taking new forms. This work contributes to the paradigm shifts regarding deaf emancipation and deaf education taking place around the world"--